Exploring the Role of Vocational High Schools in Fostering Entrepreneurial Mindset and Skills in Medan City - Luqman, Faizal; Sugiarto, Lilik (Islamic Educational Management Programme, 2022)
Transferring vocational entrepreneurship education to various contexts necessitates extensive localization. This paper examines the challenges and considerations associated with transferring vocational entrepreneurship training to diverse regions and emphasizes the significance of adapting the training to meet the specific needs and demands of the target region. It highlights the importance of understanding the local economic, social, and cultural landscapes in order to tailor the training program effectively. The availability and accessibility of resources, such as technology and funding, are also discussed as essential adaptation factors. Engaging local stakeholders, such as governments, educational institutions, and industry associations, is emphasized as a crucial element for assuring the relevance and sustainability of training. In addition, the paper emphasizes the significance of continuous evaluation and feedback mechanisms to monitor the outcomes and impact of transferred training and make adjustments as necessary. By addressing these factors and adapting vocational entrepreneurship training to local conditions, it can contribute to the empowerment of individuals, the promotion of economic development, and the cultivation of thriving entrepreneurial ecosystems in a variety of regions.